Identification of Independent Streptococcus gordonii SspA and SspB Functions in Coaggregation with Actinomyces naeslundii - Egland, Paul G. (American Society for Microbiology, 2001)
The initial stages of dental plaque formation involve the adherence of early colonizing organisms such as Streptococcus gordonii and Actinomyces naeslundii to the saliva-coated tooth surface and to each other. The S. gordonii surface proteins SspA and SspB are known to play a role in adherence to salivary proteins and mediate coaggregation with other bacteria. Coaggregation is the adhesin receptor-mediated interaction between genetically distinct cell types and appears to be ubiquitous among oral isolates. To define the function of SspA and SspB separately on the surface of their natural host, we constructed and analyzed the coaggregation properties of an isogenic sspB mutant of S. gordonii DL1, an sspAB double mutant, and a previously described sspA mutant. A. naeslundii strains have been previously classified into six coaggregation groups based on the nature of their coaggregations with S. gordonii DL1 and other oral streptococci. Coaggregation assays with the sspA and sspB mutants showed that SspA and SspB are the streptococcal proteins primarily responsible for defining these coaggregation groups and, thus, are highly significant in the establishment of early dental plaque. SspA exhibited two coaggregation-specific functions. It participated in lactose-inhibitable and -noninhibitable interactions, while SspB mediated only lactose-noninhibitable coaggregations. Accordingly, the sspAB double mutant lacked these functions and allowed us to detect a third coaggregation interaction with one of these organisms. These proteins may play an important role in development of S. gordonii-A. naeslundii communities in early dental plaque. Understanding these adhesin proteins will aid investigations of complex microbial communities that characterize periodontal diseases.